Preliminary discovery of novel markers for human cell line activation test (h-CLAT). (August 2021) - Karkhanis, Aneesh V.; Chan, Eric Chun Yong; Ren, Ee Chee
Abstract: The human cell line activation test (h-CLAT) is an OECD approved (Test No. 442E) assay to identify novel skin sensitizers. h-CLAT simulates dendritic cell activation in the skin sensitization pathway and is based on the measurement of CD54 and CD86 overexpression on monocytic, leukemic THP-1 cells. However, the current h-CLAT markers show inconsistent results with moderate and weak sensitizers. Moreover, these markers have accessory roles in cell adhesion and signaling rather than a direct role in cellular inflammation. Therefore, we have explored other inflammation-related markers in this study. PBMCs comprises a mixture of cells that resemble the complex immunological milieu in adults and were primarily used to identify markers. PBMCs ( n  = 10) and THP-1 cells were treated with 1-chloro-2, 4-dinitrobenzene (DNCB, strong) and NiCl2 (Ni, moderate) sensitizers or DMSO (control) and incubated for 24 h. The samples were subjected to RNA sequencing to obtain log2 fold change in gene expression. DNCB and NiCl2 significantly upregulated 80 genes in both cell types. Of these, CD109, CD181, CD183, CLEC5A, CLEC8A & CD354 were experimentally validated. DNCB and Ni but not isopropyl alcohol (non-sensitizer) significantly induced the expression of all novel markers except CLEC8A. Moreover, the percentage induction of all novel markers except CLEC8A satisfied the OECD acceptance criteria. In summary, we identified five novel markers that may supplement the current repertoire of h-CLAT markers. Highlights: Discovered five novel h-CLAT markers namely CD109, CD181, CD183, CLEC5A, CD354. The % relative fluorescence intensity for novel markers satisfies the OECD cut-off. The performance of novel and existing h-CLAT markers is comparable.